Iron, carotene, and ascorbic acid in cassava roots and leaves - Chavez, Alba L.; Bedoya Flores, JM; Sánchez, T.; Iglesias, C.A.; Ceballos, H.; Roca, W. (2000)
The cassava core collection (601 genotypes) was evaluated for root and leaf contents of micronutrient minerals, ascorbic acid, and carotene. Wide genetic variability was observed for all measurements, indicating that there is good potential for exploiting and improving the nutritive value of cassava. There seems to be little correlation between the levels of any micronutrient in roots and leaves. There was no clear association between carotene and ascorbic acid concentrations. A genetic study of the progeny of a cross between yellow and white parents indicated control of the yellow trait by only two genes. The stability of vitamins after three commonly used processing procedures was evaluated in a sample of 26 genotypes. A higher proportion of the original vitamin content survived boiling, whereas solar drying resulted in the highest losses. Carotene was more stable than ascorbic acid. In a limited number of lines, there was some indication that higher vitamin content was associated with decreased post-harvest physiological deterioration. Since it is well established that ?-carotene and ascorbic acid can enhance the absorption and internal transport of dietary iron and zinc from plant sources, yellow varieties of cassava have potential to address not only vitamin deficiencies per se, but also iron-deficiency anaemia and zinc deficiency. Further, the use of the leaves as a vegetable, as is done in several African countries, can complement the use of the root as a staple because of the high nutrient density of the leaves. The potential to improve the nutritive potential of cassava is exciting.